Study the Physiological and Histological Effects of Moringa oleifera alcoholic Extract to Reduce the Harmful Effects of Red Lead Oxide in Male Albino Mice - Ghaidan, Hajer Qais; Al-Dhamin, Ahmed Saad Abdulwahhab (Iraqi Journal of Science, 2024)
This study included investigating red lead oxide effects on the bodies of laboratory animals (Albino mice) and how to remove or reduce the effect of this pollutant that was dosed orally using the ethanolic extract of the Moringa oleifera (MO) plant. In the study, 40 adult male mice were used. At an average age of 8-10 weeks and with 21-29 grams average weight, the animals were randomly distributed among four groups with 10 mice/group. The first group M1 was the control group, the second group M2 was treated with red lead oxide only [1.25 mg/kg], while the third group M3 was treated with red lead oxide + Moringa oleifera [C1 = 8.4 mg/kg], and the last group M4 was treated with red lead oxide + Moringa oleifera [C2 = 9 mg/kg]. The results showed a significant difference increase in the growth rates of laboratory mice (p≤0.05) for all studied groups, while the results of animals exposed to red lead oxide and treated with MO extract and those exposed to red lead oxide only showed a significant difference increase (p≤0.01) compared to the control group. In addition, the results of the FBS analysis showed that there was a highly significant increased (p≤0.01) among the four groups that were mentioned earlier and when compared to the control group. The histological examination sections showed different changes in the tissues of the liver, pancreas and kidneys of the mice. The results of this study indicated that an extract of MO, is important to reduce the adverse effects of exposure to red lead oxide toxicity. The administration of MO returned some parameters to control, especially histological sections. It showed that red lead oxide had a harmful effect on tissue sections, while MO plant extract reduced the toxicity of red lead oxide for the M3 and M4 groups.